Provisional checklist of freshwater fish diversity and distribution in Perak, Malaysia, and some latest taxonomic concerns - Ng, Casey Keat Chuan; Lim, Teow Yeong; Ahmad, Amirrudin B.; Khaironizam, Md Zain (Zootaxa, 2019)
This study investigates the published literature and incorporates our field data from 1997 to September 2018 to generate an inventory report of primary freshwater fishes for Perak State in Malaysia. We critically examined and enumerated 186 species from 2 classes, 16 orders, 43 families and 114 genera in 57 localities. A total of 173 fish species (91.4%) are native to Perak and 17 species (8.6%) are non-native. The provisional checklist presented herein is conservative and excludes doubtful inventory records that lack synthesis and traceability. We encountered seven taxonomic discrepancies and we also could not confidently identify eight species. These are explicitly discussed to inform future workers.